The mapping of the historical-educational tachings present in the italian university education. A brief premise of method - Borruso, Francesca; Elia, Domenico Francesco Antonio; Pruneri, Fabio (Rivista di Storia dell’Educazione, 2019)
This is an analytical report and an hermeneutical/interpretative analysis of the data collected in our research. We verify the percentage presence of teachings belonging to the scientific-disciplinary area M-Ped/02 at Italian universities. Then we identify the articulations of the scientific/disciplinary area in the various courses provid and if the teaching assignments to teachers respected the scientific-disciplinary relevance.